REX-001, a BM-MNC Enriched Solution, Induces Revascularization of Ischemic Tissues in a Murine Model of Chronic Limb-Threatening Ischemia - Rojas-Torres, Marta; Jiménez-Palomares, Margarita; Martín-Ramírez, Javier; Beltrán-Camacho, Lucía; Sánchez-Gomar, Ismael; Eslava-Alcon, Sara; Rosal-Vela, Antonio; Gavaldá, Sandra; Durán-Ruiz, Mª Carmen (Frontiers in Cell and Developmental Biology, 2020)
Background: Bone Marrow Mononuclear Cells (BM-MNC) constitute a promising alternative for the treatment of Chronic Limb-Threatening ischemia (CLTI), a disease characterized by extensive blockade of peripheral arteries, clinically presenting as excruciating pain at rest and ischemic ulcers which may lead to gangrene and amputation. BM-MNC implantation has shown to be efficient in promoting angiogenesis and ameliorating ischemic symptoms in CLTI patients. However, the variability seen between clinical trials makes necessary a further understanding of the mechanisms of action of BM-MNC, and moreover, to improve trial characteristics such as endpoints, inclusion/exclusion criteria or drug product compositions, in order to implement their use as stem-cell therapy. Materials: Herein, the effect of REX-001, a human-BM derived cell suspension enriched for mononuclear cells, granulocytes and CD34+ cells, has been assessed in a murine model of CLTI. In addition, a REX-001 placebo solution containing BM-derived red blood cells (BM-RBCs) was also tested. Thus, 24 hours after double ligation of the femoral artery, REX-001 and placebo were administrated intramuscularly to Balb-c nude mice (n:51) and follow-up of ischemic symptoms (blood flow perfusion, motility, ulceration and necrosis) was carried out for 21 days. The number of vessels and vascular diameter sizes were measured within the ischemic tissues to evaluate neovascularization and arteriogenesis. Finally, several cell-tracking assays were performed to evaluate potential biodistribution of these cells. Results: REX-001 induced a significant recovery of blood flow by increasing vascular density within the ischemic limbs, with no cell translocation to other organs. Moreover, cell tracking assays confirmed a decrease in the number of infused cells after 2 weeks post-injection despite on-going revascularization, suggesting a paracrine mechanism of action. Conclusion: Overall, our data supported the role of REX-001 product to improve revascularization and ischemic reperfusion in CLTI.